Духless, или Повесть о ненастоящем человеке - Минаев Сергей Сергеевич (АСТ, 2011)
Экземпляры: ф13 (20170119) / Инвентарный номер: 53257 / Цена: 70.00 / Сис.шифр: Р2 / Авт.знак: М 61 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6